Prevalencia de enfermedad arterial periférica mediante determinación del índice tobillo brazo en los pacientes mayores de 50 años atendidos en el Hospital del IESS Manuel Ygnacio Monteros en el periodo enero a junio de 2014 - Aguirre Esparza, Karla Lisbeth (2014)
This study looks to discover through the ankle-brachial index, the prevalence of peripheral artery disease (PAD) in patients older than 50 years hospitalized in the clinic of Manuel Ygnacio Monteros Hospital; furthermore, it looks to identify the number of illnesses associated with peripheral artery disease that affects each of the individuals; determine the percentage of patients with symptoms associated with peripheral arterial disease and establish gender and age group present greater severity and morbidity. Is descriptive transversal. This is shown with a sample size of 156 people, including 72 patients. The selection of these patients was done in accordance with inclusion criteria. For the use of the ABI, a handheld, 8-MHz, one-directional Doppler gauge was used, along with a calibrated mercury sphygmometer. Of the 72 patients, the prevalence of PAD was 42%; the 51% were women and 49% men. 33% had a medium to moderate degree of PAD. The prevalence of other chronic illnesses was: 31% suffered from hypertension, 41% were diabetic, 17% suffered from dyslipidemia, 7% were obese, and 3% were smokers. 14.1% presented up to three associated illnesses. Furthermore in this study 79% of the patients presented some type of symptom associated with PAD. It was determined that patients with higher prevalence of peripheral arterial disease were females, in an age group between the ages of 66-70 years, of which a quarter had no associated symptoms. Because of its low cost and ease of application of the technique, the ABI should be a method available and routinely used in Primary Care. Key words: Ankle-Brachial Index (ABI), chronic illnesses, Manuel Ygnacio Monteros Hospital, Peripheral Artery Disease (PAD).